THE EFFECTIVENESS OF QUESTION-ANSWER RELATIONSHIP (QAR) STRATEGY IN ENHANCING STUDENTS’ READING COMPREHENSION ABILITIES - Daflizar Daflizar; Maria Roza (PROJECT (Professional Journal of English Education), 2022)
The study reported here aimed to examine the effectiveness of the Question-Answer Relationship (QAR) strategy on students’ ability in comprehending narrative texts. Using a quasi-experimental method, this study compared two English classes: one was assigned as the experimental group and the other as the control group, in terms of reading comprehension improvement, which was measured through a pretest and posttest. The study involved a total of 46 eighth-graders of a junior high school in Kerinci regency, Jambi Province, Indonesia. The control group was taught using a conventional strategy while the experiment group was engaged in the QAR strategy to answer reading comprehension questions of narrative texts. The findings revealed that the QAR strategy was effective in enhancing students’ scores in reading comprehension, which was indicated by a significant difference in the pretest and posttest scores of the experimental group. The findings of this study add to the current literature on the significance of using the QAR strategy to foster student reading. Practical implications for EFL teaching in the Indonesian context are put forward. Keywords:  Effectiveness, Question-Answer Relationship (QAR) Strategy, Reading Comprehension, Narrative Texts